Comparative Associations of Muscle Mass and Muscle Strength with Mortality in Dialysis Patients - Isoyama, Naohito (American Society of Nephrology, 2014)
BACKGROUND AND OBJECTIVES: Reduced muscle mass and strength are prevalent conditions in dialysis patients. However, muscle strength and muscle mass are not congruent; muscle strength can diminish even though muscle mass is maintained or increased. This study addresses phenotype and mortality associations of these muscle dysfunction entities alone or in combination (i.e., concurrent loss of muscle mass and strength/mobility, here defined as sarcopenia). DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This study included 330 incident dialysis patients (203 men, mean age 53±13 years, and mean GFR 7±2 ml/min per 1.73 m(2)) recruited between 1994 and 2010 and followed prospectively for up to 5 years. Low muscle mass (by dual-energy x-ray absorptiometry appendicular mass index) and low muscle strength (by handgrip) were defined against young reference populations according to the European Working Group on Sarcopenia in Older People. RESULTS: Whereas 20% of patients had sarcopenia, low muscle mass and low muscle strength alone were observed in a further 24% and 15% of patients, respectively. Old age, comorbidities, protein-energy wasting, physical inactivity, low albumin, and inflammation associated with low muscle strength, but not with low muscle mass (multivariate ANOVA interactions). During follow-up, 95 patients (29%) died and both conditions associated with mortality as separate entities. When combined, individuals with low muscle mass alone were not at increased risk of mortality (adjusted hazard ratio [HR], 1.23; 95% confidence interval [95% CI], 0.56 to 2.67). Individuals with low muscle strength were at increased risk, irrespective of their muscle stores being appropriate (HR, 1.98; 95% CI, 1.01 to 3.87) or low (HR, 1.93; 95% CI, 1.01 to 3.71). CONCLUSIONS: Low muscle strength was more strongly associated with aging, protein-energy wasting, physical inactivity, inflammation, and mortality than low muscle mass. Assessment of muscle functionality may provide additional diagnostic and prognostic information to muscle-mass evaluation.